FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN WISATAWAN MENGGUNAKAN TRANSPORTASI BERBASIS APLIKASI DI PT. GOJEK INDONESIA - Nora Ronia Pangaribuan; Ni Made Sofia Wijaya; Ni Putu Eka Mahadewi (Jurnal IPTA (Industri Perjalanan Wisata), 2016)
Nowadays, internet is an essential contribution to tourism development. The internet offers the potential to make the information and booking facilities. It also provides a tool a communication between tourism suppliers, intermediaries, as well as end-consumers. Gojek is one of transport based application that is currently used by tourists to take advantage of low cost offered. The purpose of this research is to determine the affecting and dominant factor in affecting tourist's decision to use GoJek application. Data were collected through questionnaires, interviews, literature study and documentation. Sample of this research used purposive sampling technique with number of sampling are 100 respondents, focused on tourists who have been using the GoJek application. This research used six factors which consist of seventeen indicators. The results of factors analyzed affecting interpreted as external factors, psychological, internal, motivation and labor saving. The most dominant factor is external consists by a variable reference, cultural, economic, price competition, perception of security and internet trusted. Factors which eliminated in this research is use every time because tourists not necessarily used GoJek application at any time for order transportation while holiday in Bali.